Struktur Komunitas Padang Lamun Di Perairan Gili Air, Lombok Utara - Ibadur Rahman; Nurliah; Edwin Jefri; Chandrika Eka Larasati (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
Seagrass is a coastal ecosystem that has important role as a feeding ground, a spawning ground and a nursery ground for various marine biota. This study aims to examine the biodiversity of seagrass at Gili Air, North Lombok Regency, West Nusa Tenggara. This study was conducted to observe the cover percentage of seagrass, it's composition, the number of seagrass stands, canopy's height, frequency of seagrass presence, and index of importance of seagrass. Seagrass data was collected using a 50cm x 50cm quadrant transect, with a total area of 100 m2, referring to the monitoring standards set by SeagrassNet. Water quality analysis was carried out at the Bioecology Laboratory of the Aquaculture Study Program, University of Mataram, and at the Laboratory of the Marine Aquaculture Center (BPBL) of Sekotong, West Lombok. The results showed that the seagrass communities in Gili Air waters were composed of 5 (five) species: Halophila ovalis, Thalassia hemperichii, Cymodocea rotundata, Halodulea pinifolia, and Halodule uninervis, with the percentage of coverage ranging from 26.88-39.17%, and the average coverage by 31.53%. Thalassia hemperichii is the species that has the highest contribution to the seagrass community at Gili Air.